Since the two lines are parallel, the angle labeled 130 is congruent to the angle labeled x+ 136 so you can set them equal to each other
130 = x + 136
subtract 136 from both sides
x = -6
Answer:
A) 0.2g
Step-by-step explanation:
![{.}](https://tex.z-dn.net/?f=%7B.%7D)
So, the definite integral ![\int\limits^1_0 {(4 - 6x^{2} )} \, dx= - 74](https://tex.z-dn.net/?f=%5Cint%5Climits%5E1_0%20%7B%284%20-%206x%5E%7B2%7D%20%29%7D%20%5C%2C%20dx%3D%20-%2074)
Given that
We find
![\int\limits^1_0 {(4 - 6x^{2} )} \, dx](https://tex.z-dn.net/?f=%5Cint%5Climits%5E1_0%20%7B%284%20-%206x%5E%7B2%7D%20%29%7D%20%5C%2C%20dx)
<h3>Definite integrals </h3>
Definite integrals are integral values that are obtained by integrating a function between two values.
So, ![Integral \int\limits^1_0 {(4 - 6x^{2} )} \, dx](https://tex.z-dn.net/?f=Integral%20%5Cint%5Climits%5E1_0%20%7B%284%20-%206x%5E%7B2%7D%20%29%7D%20%5C%2C%20dx)
So, ![\int\limits^1_0 {(4 - 6x^{2} )} \, dx = \int\limits^1_0 {4} \, dx - \int\limits^1_0 {6x^{2} } \, dx \\= 4[x]^{1}_{0} - \int\limits^1_0 {6x^{2} } \, dx \\= 4[x]^{1}_{0} - 6\int\limits^1_0 {x^{2} } \, dx \\= 4[1 - 0] - 6\int\limits^1_0 {x^{2} } \, dx\\= 4[1] - 6\int\limits^1_0 {x^{2} } \, dx\\= 4 - 6\int\limits^1_0 {x^{2} } \, dx](https://tex.z-dn.net/?f=%5Cint%5Climits%5E1_0%20%7B%284%20-%206x%5E%7B2%7D%20%29%7D%20%5C%2C%20dx%20%3D%20%5Cint%5Climits%5E1_0%20%7B4%7D%20%5C%2C%20dx%20-%20%5Cint%5Climits%5E1_0%20%7B6x%5E%7B2%7D%20%7D%20%5C%2C%20dx%20%5C%5C%3D%20%204%5Bx%5D%5E%7B1%7D_%7B0%7D%20%20%20%20-%20%5Cint%5Climits%5E1_0%20%7B6x%5E%7B2%7D%20%7D%20%5C%2C%20dx%20%5C%5C%3D%20%204%5Bx%5D%5E%7B1%7D_%7B0%7D%20%20%20%20-%206%5Cint%5Climits%5E1_0%20%7Bx%5E%7B2%7D%20%7D%20%5C%2C%20dx%20%5C%5C%3D%204%5B1%20-%200%5D%20%20%20%20-%206%5Cint%5Climits%5E1_0%20%7Bx%5E%7B2%7D%20%7D%20%5C%2C%20dx%5C%5C%3D%204%5B1%5D%20%20%20%20-%206%5Cint%5Climits%5E1_0%20%7Bx%5E%7B2%7D%20%7D%20%5C%2C%20dx%5C%5C%3D%204%20%20%20%20-%206%5Cint%5Climits%5E1_0%20%7Bx%5E%7B2%7D%20%7D%20%5C%2C%20dx)
Since
,
Substituting this into the equation the equation, we have
![\int\limits^1_0 {(4 - 6x^{2} )} \, dx = 4 - 6\int\limits^1_0 {x^{2} } \, dx\\= 4 - 6 X 13 \\= 4 - 78\\= -74](https://tex.z-dn.net/?f=%5Cint%5Climits%5E1_0%20%7B%284%20-%206x%5E%7B2%7D%20%29%7D%20%5C%2C%20dx%20%3D%204%20-%206%5Cint%5Climits%5E1_0%20%7Bx%5E%7B2%7D%20%7D%20%5C%2C%20dx%5C%5C%3D%204%20-%206%20X%2013%20%5C%5C%3D%204%20-%2078%5C%5C%3D%20-74)
So, ![\int\limits^1_0 {(4 - 6x^{2} )} \, dx= - 74](https://tex.z-dn.net/?f=%5Cint%5Climits%5E1_0%20%7B%284%20-%206x%5E%7B2%7D%20%29%7D%20%5C%2C%20dx%3D%20-%2074)
Learn more about definite integrals here:
brainly.com/question/17074932